Failure Tree Analysis of CNC Plasma Cutting Machine for Occupational Safety on Shipyard - Mochamad Yusuf Santoso; Aulia Nadia Rachmat; Amalia Rahma Fauzia (International Journal of Marine Engineering Innovation and Research, 2024)
The advancement of ship production technology in Indonesia involves the implementation of modern techniques integrating computer-based design and production facilities, such as Computer-Aided Manufacturing (CAM) for operating production machines utilizing Computer Numerical Control (CNC). One specific type of CNC machine utilized in ship production is the plasma cutting CNC machine. Despite being crucial to production, these machines frequently encounter failures that impede the production process. Through prior failure analyses conducted by the company, it has been identified that the dust collector air hose component exhibits the highest failure rate with six distinct failure modes. This article conducts qualitative and quantitative analyses of the causes of failure in the air hose dust collector of CNC plasma cutting machines using the Fault Tree Analysis (FTA) method. FTA is employed as a method to ascertain the fundamental causes of the event. The analysis results are utilized to provide recommendations for controlling objectives related to occupational safety. Six failure trees are generated, comprising a total of 28 basic causes. The most frequently occurring types of basic causes are associated with workers, methods, and materials. The probability of occurrence for the minimal cut set of each failure tree has been successfully computed. These calculations reveal that all top events possess probability values exceeding 76%. Specifically, the event of the dust collector air gap breaking has the highest probability value, reaching 99.88%, which is a composite of 15 basic causes. Control recommendations are provided in the form of substitution, engineering solutions, and administrative controls.